Variable-number tandem repeat markers for Mycobacterium intracellulare genotyping: comparison to the 16S rRNA gene sequencing - Kaisen Chen; Yangyi Zhang; Yiping Peng (Journal of Infection in Developing Countries)
Introduction: Characterizing Mycobacterium intracellulare responsible for nontuberculous mycobacterial (NTM) infections may aid in controlling outbreaks. This study aimed to compare 16S ribosomal ribonucleic acid (rRNA) sequencing and variable-number tandem repeat (VNTR) genotyping of M. intracellulare strains isolated from clinical samples, and to characterize VNTR clusters associated with NTM infections or cavity formation. Methodology: Sputum samples were obtained from 77 HIV-negative patients with pulmonary disease between 2009 and 2013. One M. intracellulare strain was isolated from each patient and genotyped using 16S rRNA and eight loci VNTR sequencing. Results: Single nucleotide polymorphism (SNP) genotyping identified seven point mutations at nucleotide positions 101, 178, 190, 252, 382, 443, and 490 in 16S rRNA, and four SNP patterns were identified: type 1 (16 strains), 2 (41 strains), 3 (11 strains), and 4 (1 strain); 5 strains had unique SNP patterns. VNTR genotyping identified VNTR12 as the most discriminating marker (allelic diversity 0.692). VNTR3 was the most homogeneous marker (allelic diversity 0.518), but each locus had high discriminating ability. The 77 strains were clustered according to the unpaired group method using arithmetic averages: cluster 1 (17 strains), 2 (43 strains), 3 (9 strains), and 4 (4 strains); 4strains had unique SNP patterns. Overall, over 90% strains were matched to similar SNP and VNTR groupings. VNTR clusters were associated with NTM infection (p =0.007) and presence of a cavity (p =0.042). Both methods distinguished four subtypes of M. intracellulare, which corresponded. Conclusions: VNTRs may represent an effective, user-friendly, low-cost typing technique.